Francisella noatunensis subspecies noatunensis clpB deletion mutant impairs development of francisellosis in a zebrafish model. Issue 52 (19th December 2017) - Lampe, Elisabeth O.; Zingmark, Carl; Tandberg, Julia I.; Thrane, Ida Marie P.; Brudal, Espen; Sjöstedt, Anders; Winther-Larsen, Hanne C.
Abstract: Background: Francisella noatunensis ssp. noatunensis ( F.n.n. ) is the causative agent of francisellosis in Atlantic cod and constitutes one of the main challenges for future aquaculture on this species. A facultative intracellular bacterium like F.n.n. exert an immunologic challenge against which live attenuated vaccines in general are most effective. Thus, we constructed a deletion in the F.n.n. clpB gene as Δ clpB mutants are among the most promising vaccine candidates in human pathogenic Francisella . Purpose: Characterization of F.n.n. Δ clpB using primary Atlantic cod head kidney leukocytes, the zebrafish embryo and adult zebrafish model with focus on potential attenuation, relevant immune responses and immunogenic potential. Main results: Interleukin 1 beta transcription in Atlantic cod leukocytes was significantly elevated from 24 to 96 h post infection with F.n.n. Δ clpB compared to F.n.n. wild-type (wt) . Growth attenuation of the deletion mutant in zebrafish embryos was observed by fluorescence microscopy and confirmed by genome quantification by qPCR. In the immunization experiment, adult zebrafish were immunized with 7 × 10 6 CFU of F.n.n. Δ clpB before challenge four weeks later with 6 × 10 8 CFU of F.n.n. wt. One day after challenge, immunized zebrafish responded with significantly lower interleukin 8 levels compared to the non-immunized control. Immunized fish were protected against the acute mortality observed in non-immunized zebrafish after challenge and bacterial genomes quantified by qPCR were reduced to a minimum 28 days post challenge, indicating protective immunity stimulated by F.n.n. Δ clpB . Conclusion: Deletion mutation of clpB in F.n.n. causes in vitro and in vivo attenuation and elicits a protective immune response in adult zebrafish against a lethal dose of F.n.n. wt. Taken together, the results presented increases the knowledge on protective immune responses against F.n.n .